1995
DOI: 10.1084/jem.182.6.1727
|View full text |Cite
|
Sign up to set email alerts
|

Activation of virus replication after vaccination of HIV-1-infected individuals.

Abstract: SummaryLittle is known about the factors that govern the level of HIV-1 replication in infected individuals. Recent studies (using potent antiviral drugs) of the kinetics of HIV-1 replication in vivo have demonstrated that steady-state levels of viremia are sustained by continuous rounds of de novo infection and the associated rapid turnover of CD4 + T lymphocytes . However, no information is available concerning the biologic variables that determine the size of the pool ofT cells that are susceptible to virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
144
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(162 citation statements)
references
References 46 publications
11
144
0
7
Order By: Relevance
“…Based on these observations, our experiments suggest that T cell activation may render the cell susceptible for HIV entry due to an increased expression of cell surface CD4. Indeed, previous studies have shown that activation of T cells strongly contributes to HIV replication (73)(74)(75)(76)(77). Up to now, however, these findings have been explained by an interplay of viral and host regulatory proteins, such as Tat, Rev, Nef, NF-B, and NF-AT.…”
Section: Discussionmentioning
confidence: 71%
“…Based on these observations, our experiments suggest that T cell activation may render the cell susceptible for HIV entry due to an increased expression of cell surface CD4. Indeed, previous studies have shown that activation of T cells strongly contributes to HIV replication (73)(74)(75)(76)(77). Up to now, however, these findings have been explained by an interplay of viral and host regulatory proteins, such as Tat, Rev, Nef, NF-B, and NF-AT.…”
Section: Discussionmentioning
confidence: 71%
“…Lymphocyte stimulation by VV superinfection did not increase the virus load in monkeys infected with attenuated immunodeficiency viruses. In contrast, as shown for HIV-1 in immune-activated humans (O'Brien et al, 1995 ;Staprans et al, 1995 ;Stanley et al, 1996 ;Ro$ sok et al, 1996), in two macaques pathogenic SIV could temporarily be reactivated in vivo. Similar findings have been made by immune activation of macaques infected with pathogenic SIV during the primary phase of infection (Villinger et al, 1996).…”
mentioning
confidence: 85%
“…This was shown for HIVseropositive individuals immunized with different common vaccines (O'Brien et al, 1995 ;Staprans et al, 1995 ;Stanley et al, 1996 ;Ro$ sok et al, 1996) or super-infected with immunestimulating bacteria (Goletti et al, 1996). In these reports, enhancement of virus replication seems to contribute to AIDS pathogenesis.…”
mentioning
confidence: 99%
“…The observation of Di Mascio et al (2003a) that blip frequency is inversely correlated with baseline CD4+ T cell count suggests that patient specific factors, such as susceptibility to infection, which increases at low CD4 counts, may play a role in blip generation. Prior work on untreated, chronically infected HIV patients documents increases in viral load associated with vaccination (O'Brien et al, 1995; Staprans et al, 1995;Brichacek et al, 1996;Stanley et al, 1996) and with opportunistic infection (e.g., Donovan et al, 1996). McLean and Nowak (1992) proposed some of the first models of enhanced HIV replication due to immune stimulation via opportunistic infection, and showed how the positive feedback between enhanced HIV replication and incomplete immune control of pathogens due to HIV-immunosuppression leads finally to immune failure and full-blown AIDS.…”
Section: Introductionmentioning
confidence: 99%